The impact of digitalisation on banking industry in Malaysia: opportunities, challenges, and way forward - Loh, Jian Long (2024)
The banking industry in Malaysia is undergoing a significant transformation as a result of the worldwide digital revolution. This research investigates the diverse effects of digitalization on the banking sector in Malaysia, examining the many possibilities and difficulties that arise as a result. The emergence of digital banking has facilitated the advancement of operational effectiveness, customer-focused strategies, and improved financial accessibility, namely with the introduction of e-wallets and mobile banking services that cater to those who were previously excluded from traditional banking systems. Simultaneously, the emergence of fintech firms has engendered a competitive but cooperative atmosphere, pushing conventional banks to pursue heightened levels of innovation. Nevertheless, the expedition is not without obstacles. Prominent obstacles have arisen in the form of cybersecurity concerns, legislative issues, and infrastructure problems. Moreover, the digital gap, characterized by disparities in technological adaption among different generations, presents a distinctive and significant problem. This research further examines the potential future of the banking sector in relation to the aforementioned digital transformations, underscoring the need for banks to take a proactive stance in incorporating digital innovations, strengthening security protocols, and establishing strategic partnerships. At this critical moment, the trajectory of Malaysia's future will be shaped by the banking industry's ability to effectively handle the ongoing digital transformation, while simultaneously fostering development and diversity.